2016
DOI: 10.1177/1932296816654161
|View full text |Cite
|
Sign up to set email alerts
|

How Much Is Short-Term Glucose Prediction in Type 1 Diabetes Improved by Adding Insulin Delivery and Meal Content Information to CGM Data? A Proof-of-Concept Study

Abstract: Background: In type 1 diabetes (T1D) management, short-term glucose prediction can allow to anticipate therapeutic decisions when hypo/hyperglycemia is imminent. Literature prediction methods mainly use past continuous glucose monitoring (CGM) readings. Sophisticated algorithms can use information on insulin delivered and meal carbohydrate (CHO) content. The quantification of how much insulin and CHO information improves glucose prediction is missing in the literature and is investigated, in an open-loop setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Literature studies have shown that the performance of glucose prediction algorithms can significantly improve when additional inputs are considered apart from CGM, like insulin, meals, and physical activity, all factors that strongly impact glycemic excursions [50–52]. Some literature studies on basal insulin attenuation algorithms have explored the possibility of enhancing glucose prediction by taking into account insulin data [22, 26] and historical CGM data [25].…”
Section: Resultsmentioning
confidence: 99%
“…Literature studies have shown that the performance of glucose prediction algorithms can significantly improve when additional inputs are considered apart from CGM, like insulin, meals, and physical activity, all factors that strongly impact glycemic excursions [50–52]. Some literature studies on basal insulin attenuation algorithms have explored the possibility of enhancing glucose prediction by taking into account insulin data [22, 26] and historical CGM data [25].…”
Section: Resultsmentioning
confidence: 99%
“…While, others use CGM data plus external inputs, such as the amount of ingested carbohydrates, injected insulin and physical activity [ 52 ]. These have been shown to enhance the performance of predictions when compared to predictions using only CGM data [ 53 ].…”
Section: Glucose Predictionmentioning
confidence: 99%
“…This type of algorithm has recently been included in a prototype of a mobile DSS to support patients with T1D in daily management decisions [ 56 ]. More recently, Zecchin et al [ 53 ] have proposed using a jump NN, i.e., an NN with inputs directly connected to both the hidden layer and the output, and with four inputs: CGM reading, its first-order derivative, injected insulin and ingested carbohydrates.…”
Section: Glucose Predictionmentioning
confidence: 99%
“…It is worth noting that more sophisticated prediction algorithms, also exploiting other signals like the amount of insulin injected or physical activity, can be employed, e.g., those of Zhao et al [9,12], Zecchin et al [13,41], Turksoy et al [10], Zarkogianni et al [11], and Georga et al [42,43]. …”
Section: The Past: the “Smart” Cgm Sensormentioning
confidence: 99%
“…From a clinical point of view, it has been widely demonstrated that the additional information provided by CGM sensors, when used in conjunction with SMBG data, improves the quality of glucose control [7,8]. From an academic point of view, the availability of CGM data stimulated, over the last 15 years, the development of several CGM-based applications, e.g., algorithms for the prediction of future glucose concentration to generate preventive hypo/hyperglycemic alerts [9,10,11,12,13], for the real-time modulation of the basal insulin administration [14,15,16], and for the detection of faults with glucose sensor–insulin pumps system [17,18,19,20,21]. Even more interesting is that CGM sensors enabled the realization of the artificial pancreas (AP), i.e., a device designed mainly for Type 1 diabetes (T1D), which is aimed at maintaining the BG concentration within the safety range by automatically injecting insulin via an insulin pump controlled by a closed-loop control algorithm [22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%